STRUCTURE OF THE ORGANIZATIONAL STRUCTURE OF THE ENTERPRISE ACCORDING TO A PROCESS-ORIENTED APPROACH IN THE CONDITIONS OF DIGITALIZATION - Viktor V. Buleіchenko; Valentyna A. Pavlova (European Vector of Economic Development)
The article examines the features of choosing and building modern organizational structures of enterprise management. On the basis of the systematization of modern concepts of the formation of types of organizational structures of enterprise management, the most acceptable structures according to the process-oriented models of enterprise development and the influence on the choice of digitalization of the main activity processes were selected. It was established that the formation of organizational management structures should be considered through the prism of horizontal (flat), vertical and flexible hierarchies. Trends in the use of information and communication technologies at enterprises have been studied regarding the possibilities of digitalization and its impact on economic development. The degree of access of domestic enterprises to the Internet and the use of fixed access to it, as well as the share of employed workers who have access to the Internet of hired specialists for whom information and communication technologies are the main job, are analyzed. The peculiarities of the flat hierarchy are considered and its main characteristics are highlighted. In Ukraine, the openness of information about the company’s activities is quite limited for employees, and therefore the introduction of holacracy, which is acceptable for small and medium-sized enterprises in the service sector, is promising in the future. It was established that the vertical hierarchy in the organizational structure of enterprise management is a typical and traditional model of management, the advantages and disadvantages of the structure were determined. The concentration of power in the owner is one of the main characteristics of a vertical management structure, so owners usually choose this type of enterprise management structure. The characteristics of the vertical hierarchy are highlighted. A flexible hierarchy positioned as an adaptive structure, characterized by greater flexibility in the interaction between different levels of management, is singled out as a modern organizational structure. The main types of adaptive organizational management structures are matrix, project, program-target and coordination. The peculiarities of the types of organizational structures of enterprise management according to the process-oriented approach are compared and a number of characteristics of the positive influence of digitalization on their choice are highlighted. Demonstrably positive results of the impact of digitalization on the horizontal, vertical and flexible organizational structure of enterprise management. The shortcomings of flat, vertical and flexible hierarchies were studied and it was proved that in order to ensure the dynamic and progressive development of business entities, it is expedient to combine elements of different structures.